"I Don't Have Time to Dig Back Through This": The Role of Semantic Search in Supporting Physician Information Seeking in an Electronic Health Record. Issue 4 (2014) - Tawfik, Andrew A.; Kochendorfer, Karl M.; Saparova, Dinara; Al Ghenaimi, Said; Moore, Joi L.
Abstract The purpose of the study was twofold: to understand how usability affected physicians' performance as they used an electronic health record (EHR) and to ascertain whether use of a semantic search feature would better support physician performance during an information‐seeking task. Participants (n = 10) were asked to complete two search tasks to find pertinent patient information. In the first task, participants located the information as they normally would (through browsing the EHR). In the second task, participants employed a semantic search tool. Upon task completion, participants were interviewed to further understand their perceptions and information‐seeking behavior in an EHR. Statistically significant results confirmed that participants were able to more efficiently navigate through an EHR in terms of time and number of clicks when using the semantic search feature. Moreover, participants were more confident in the accuracy of their answers when using semantic search compared with the browsing method. Implications for practice are discussed.